Differences in the Effectiveness of Early Detection of Breast Cancer (Sadari) Learning Face to Face with Online Learning: Perbedaan Efektivitas Pembelajaran Deteksi Dini Kanker Payudara (Sadari) Face To Face dengan Online Learning - Siti Khotimah; Evin Noviana Sari (International Journal of Technology Vocational Education and Training, 2020)
Breast cancer is a type of malignant tumor that develops in breast cells. This cancer can grow if there is abnormal growth of cells in the breast. These cells divide faster than normal cells and accumulate, which then forms a lump or mass. This research method is quantitative research with Quasi Experimental Design in the form of Pre Test - Post Test Control Group Design. The results of the study found that there are significant differences between the two learning methods used. Learning using the Face To Face Learning method about early detection of breast cancer is more effective than learning using the Online Learning method, the p-value is 0,000 <0.05 in group 1 of the Face to Face Learning method and the p-value is 0.038 <0.05 in group 2 the Online Learning method. The conclusion of this study is health education learning especially about early detection of breast cancer in adolescents is more effective using face to face learning method compared to learning using the Online Learning method.